Gender differences in age of smoking initiation and its association with health. (October 2015) - Thompson, Azure B.; Tebes, Jacob K.; McKee, Sherry A.
Abstract Background: It is generally accepted that smoking starts in adolescence and earlier initiation is associated with more negative health outcomes. Some research suggests that women initiate smoking at later ages and have more negative health outcomes than men. The purpose of this study was to examine gender differences in age of initiation and its association with health. Methods: The sample included men (n = 8506) and women (n = 8479) with a history of smoking from the 2001–2002 National Epidemiological Survey of Alcohol Related Conditions. Logistic regression was used to examine gender differences in the effect of late smoking initiation on physical and mental health status after adjusting for covariates. Results: At mostly all ages after 16, women exceeded men in rates of smoking initiation (59.8% versus 50.3%, p < 0.001). Among late initiators (≥16), women were more likely than men to have hypertension (OR: 1.24, CI: 1.09–1.41), heart disease (OR: 1.20, CI: 1.00–1.45), major depressive disorder (OR: 2.54, CI: 2.22–2.92), and generalized anxiety disorder (OR: 2.34, CI: 1.84–2.99). Among early initiators (<16), women were more likely than men to have major depressive disorder (OR: 2.42, CI: 2.11–2.77) and generalized anxiety disorder (OR: 2.01, CI: 1.59–2.54) but there were no gender differences in the likelihood of having hypertension (OR: 1.04, CI: 0.89–1.22) and heart disease (OR: 1.11, CI: 0.90–1.36). Conclusions: In late adolescence and adulthood, women exceed men in smoking initiation. Late initiation was associated with more significant physical health risks for women than men. Our findings raise questions about generally accepted notions on the age at which smoking initiation occurs and its association with health.